A novel nano-magnetic heterostructure BiOCl/Co-doped SrFe12O19: synthesis and photocatalytic activity. (19th September 2019) - Qing, Duowen; Xie, Taiping; Yang, Jun; Liu, Chenglun; Xu, Longjun
ABSTRACT: The Co-doped SrFe12 O19 with small particle size was successfully synthesised via a hydrothermal method for the first time. XRD test indicated that the Co incorporation did not alter the M-type structure for SrFe12 O19 . Meanwhile, a novel nano-magnetic heterostructure BiOCl/Co-doped SrFe12 O19 (BiOCl/SrFe12-x Cox O19 ) was also synthesised using same method. The heterostructure possessed a low bandgap energy and stable magnetic property. The photocatalytic activity evaluation illustrated that the photodegradation efficiency of Rhodamine B (RhB) reached to 98% after 100-min photocatalytic reaction. Furthermore, RhB photodegradation efficiency using BiOCl/SrFe12-x Cox O19 was still more than 70% after four times reuse. The photocatalytic mechanism was explained in detail. The application of BiOCl/SrFe12-x Cox O19 into the removal of organic contaminants or the control of environmental pollution will be of great value. The research results are beneficial to the promotion of industrial applications of solid-state composites in the fields of environmental engineering and energy utilisation.